10+3h=-6+2h

Simple and best practice solution for 10+3h=-6+2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+3h=-6+2h equation:


Simplifying
10 + 3h = -6 + 2h

Solving
10 + 3h = -6 + 2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2h' to each side of the equation.
10 + 3h + -2h = -6 + 2h + -2h

Combine like terms: 3h + -2h = 1h
10 + 1h = -6 + 2h + -2h

Combine like terms: 2h + -2h = 0
10 + 1h = -6 + 0
10 + 1h = -6

Add '-10' to each side of the equation.
10 + -10 + 1h = -6 + -10

Combine like terms: 10 + -10 = 0
0 + 1h = -6 + -10
1h = -6 + -10

Combine like terms: -6 + -10 = -16
1h = -16

Divide each side by '1'.
h = -16

Simplifying
h = -16

See similar equations:

| -15x^2=12x-5 | | 3a+3b+2a= | | -17=a-3 | | 12x-12=8+6+6x | | m+4=6m-2 | | 2(2x+4)/2= | | -2=1+x | | 65X=31 | | 7+x=9+27 | | 1x+16=1x | | 5x+2(10x)+4(25x)=12.50 | | 11+5e=8+4e | | -6x+1=2x-7 | | 28-4d=-12-3p | | z+n=m | | (r-4)(r+1)+(r-4)(r+6)=0 | | 14+x=5+2x | | 3x^2+12x-64=0 | | 8.1-0.6x=7.2 | | 51+5x=24+8x | | y+23=45 | | -4*2r+-5=-44 | | 33+4x=49+2x | | y-t=-5 | | 3.4x=5 | | z+2=1 | | 3(4y-3)-(4y+4)= | | 71+2x=49+3x | | 3+8x=-48 | | C^2+4-4c=0 | | N+19=4 | | 2(3r-7)+4(3r+2)=6(5r+9)+3 |

Equations solver categories